2003
DOI: 10.1063/1.1529291
|View full text |Cite
|
Sign up to set email alerts
|

Lateral composition modulation in InAs/GaSb superlattices

Abstract: We report the analysis of lateral composition modulation in (InAs) m /(GaSb) m superlattices by x-ray diffraction. Vertical and lateral satellite peaks for a 140 period structure were observed. The lateral modulation wavelength, average superlattice composition, and vertical superlattice wavelength were determined. The lateral modulation was observed only along one in-plane direction resulting in quantum wire-like structures along the ͓110͔ direction. The unconventional structure of the lateral composition mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2003
2003
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The^10 Å variation in L SL is due to a splitting in the satellite peaks, which indicates that there are two or more discrete superlattice periods formed along the growth direction. This was evident in the XSTM images taken of the entire vertical height of the structure [14] (not shown), where the undulations did not become regular until after about 40 periods, and became irregular after 80 periods. The lateral wavelength, L LCM ¼ 554 AE 3 A; is similar in magnitude to the 100 to 400 Å wavelengths reported for other LCM systems, where it is generally found that the lateral and undulating wavelengths are identical; however, this is not the case for this sample.…”
Section: Discussionmentioning
confidence: 89%
“…The^10 Å variation in L SL is due to a splitting in the satellite peaks, which indicates that there are two or more discrete superlattice periods formed along the growth direction. This was evident in the XSTM images taken of the entire vertical height of the structure [14] (not shown), where the undulations did not become regular until after about 40 periods, and became irregular after 80 periods. The lateral wavelength, L LCM ¼ 554 AE 3 A; is similar in magnitude to the 100 to 400 Å wavelengths reported for other LCM systems, where it is generally found that the lateral and undulating wavelengths are identical; however, this is not the case for this sample.…”
Section: Discussionmentioning
confidence: 89%
“…Of particular interest are materials systems that spontaneously self-organize with a significant degree of regularity, since this periodicity can impact the electronic band structure and consequently, materials properties and device performance. Lateral composition modulation (LCM) has been reported in strained alloy systems such as bulk AlInAs and GaInP epilayers [6][7][8], as well as in intentionally grown short period superlattices such as GaP/InP, AlAs/InAs, GaAs/InAs, and InAs/GaSb [9][10][11][12]. CuPt ordering as observed in GaInP [2], GaAsP [3], GaAsSb, [4], and InAsSb [5], to microscopic dimensions on the order of ~50 nm, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, lateral composition modulation (LCM) was observed in InAs/GaSb superlattices 8,9 . LCM, which refers to the formation of phase-separated, periodic structures perpendicular to the growth direction 10 , induces changes in the physical properties of the material, i.e., The nanostructures self-organized via lateral composition modulation in 140 period (InAs)13/(GaSb)13 superlattices grown by molecular beam epitaxy have been studied by high-resolution x-ray diffraction and infrared absorption.…”
Section: Introductionmentioning
confidence: 99%